Exploring the Reactions Induced by Bioactive Glass Air Abrasion of Titanium and Their Effects on Osteoblast Cellular Responses - Abushahba, Faleh; Stiller, Adrian; Mohamad, Sherif A.; Areid, Nagat; Hupa, Leena; Heino, Terhi J.; Vallittu, Pekka K.; Närhi, Timo O. (Wiley, 2025)
This study investigated the chemical events that occur when titanium (Ti) surfaces are treated with air particle abrasion (APA) using zinc-containing bioactive glass (ZnBG), followed by immersion in simulated body fluid (SBF) for up to 96 h. The impact of these changes on osteoblast cell viability, adhesion, and differentiation was evaluated. Sandblasted and acid-etched (SA) Ti disks were subjected to APA with ZnBG particles and then immersed in SBF from 8 to 96 h. Ion dissolution and characterization of ZnBG powder and Ti disks were conducted. Analyses of osteoblast viability, adhesion, and alkaline phosphatase (ALP) activity were performed on MC3T3-E1 cells cultured on control disks (SA-Ti), as well as on ZnBG abraded disks (APA-Ti) and disks immersed for 96 h in SBF (CaP-Ti). After SBF immersion, the ZnBG particle surfaces showed a rise in Si atomic (at.)% within the first 8 h, while Ca remained stable, and the P doubled over 96 h. The ZnBG covering the disks dissolved during the first 8 h, and then the Ca, P, and Si at.% increased as the immersion time extended. The glass particles exhibited amorphous calcium–phosphate (Ca–P) layer formation after 96 h. A significantly (p = 0.004) higher cell viability level was observed on day 7 on APA-Ti compared to SA-Ti disks, while no differences in osteoblast differentiation were observed across the different surfaces. Fluorescence images demonstrated that on day 3, cells adhered to valleys and peaks of CaP-Ti threads but only to valleys on SA-Ti and APA-Ti disks. By day 7, cells were also observed on APA-Ti peaks but not on SA-Ti. In summary, APA enhanced osteoblast proliferation, and a biocompatible Ca–P layer, which formed upon mineralization, supported osteoblast viability, adhesion, and spreading.